DIPLOMASI BUDAYA INDONESIA DAN BELANDA MELALUI “UPACARA LABUH SAJI” DI PELABUHAN RATU SUKABUMI - Muhammad Daud Yusuf; Tom Finaldin (Global Mind, 2022)
Indonesian and Dutch cultural diplomacy through the "laying ceremony" at the port of Ratu Sukabumi. One of the characteristics of coastal communities is a strong dependence on the coastal environment. The good and bad of the environment will have a direct impact on their lives. The coastal communities discussed here are the people of Pelabuhan Ratu. The Pelabuhan Ratu community also has culture, namely traditional ceremonies that are still developing today in Palabuhanratu, which is often referred to as the Labuh Saji effort, Labuh Saji or called Fisherman's Day, this is a form of tradition, this tradition is carried out from generation to generation because it is believed to be an expression the gratitude of the Palabuhanratu community for the prosperity and abundant marine products and aims to honor Nyi Putri Mayangsagara or what we often hear as Nyai Ratu Kidul, of course these customs and traditions are quite interesting for the surrounding community. the coastal community of Pelabuhan Ratu in Sukabumi. The research method used is the literature review method which contains a description of the literature review that underlies the idea to solve the problem and support the theory search process. The results of the study indicate that it is true that there is a traditional culture in the Pelabuhan Ratu Sukabumi area, namely the Labuh Saji Ceremony. This tradition is carried out once a year to be exact on April 6 (Fishermen's Day).Keywords: Culture Diplomacy, Coastal Community, Pelabuhan Ratu, Labuh Saji